Analisis Biaya Operasi Teknik Off-pump CABG dibandingkan On-pump CABG Pasien BPJS Penyakit Jantung Koroner dengan Fungsi Jantung Buruk di Rumah Sakit Jantung Harapan Kita - Aris Aris; Yusi Anggriani; Hanafy Dudy Arman; Yacob Ruru (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Coronary heart disease (CHD) is a heart disease that is mainly caused by narrowing of the coronary arteries due to atherosclerosis or spam or a combination of both. In CHD patients who continued therapy, coronary artery bypass surgery can be performed Off-pump CABG or On-pump CABG, with hearts function poorly with LEF < 30 % at risk and a higher complication which results in increased costs. The research is aimed to analyze the operating cost Off-pump CABG technique compared to the On-pump CABG technique in patients with BPJS coronary heart disease with poor heart function in Rumah Sakit Jantung dan Pembuluh Darah Harapan Kita on period January – December 2015. Patient sample selection is done in the installation of medical records with the diagnosis of CHD undergoing coronary artery bypass surgery technique Off-pump CABG and On-pump CABG. Data retrieval costs of pre-operatives, peri-operatives, and post-operative. This research conducted prospectively. Data were analyzed using the Kolmogorov test, Mann Whitney test, and Kruskal Wallis test. Research results obtained from a total of 70 patients with each of the 35 patients who underwent Off-pump CABG and On-pump CABG. The average cost of technique operation Off-pump CABG amounted to Rp.85,812,864. The average cost of technique operation on-pump CABG amounted to Rp.105,480,363. Operation margin amounted to Rp. 19,667,499. Mann-Whitney test shows different averages with p-value=0,006, then there is a significant difference between the two groups. Comparison of the rates for the Ina-CBGs surgery techniques Off-pump CABG an average of Rp.141,747,683, different of Rp. 55,934,819. Of the rates for the Ina-CBGs surgery techniques on-pump CABG an average of Rp. 138,782,251, different of Rp. 33,301,888. Kruskal Wallis test shows a different averages with p-value=0,000, then there is a significant difference between the two groups. Operating cost Off-pump CABG technique is lower than of On-pump CABG surgery technique. Operating cost Off-pump CABG technique and On-pump CABG lower than tariff Ina-CBGs.